public-health-policy 2020
DOI: 10.35841/public-health-policy.4.3.30-37
|View full text |Cite
|
Sign up to set email alerts
|

Physicians intention to leave from malaysia government hospitals with existing retention strategy.

Abstract: Background: Healthcare professionals or physicians are important assets for health institutions in ensuring optimum delivery of healthcare to the people. Job satisfaction in various aspects including daily tasks, responsibilities and other duties will indirectly provide high productivity to an organization as well as ensuring a conducive working environment and reducing the resignation rates. Resignation rate trends among physicians in Malaysia ranged from 6.4% in 2000 to 3.5% in 2016. The introduction of Full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Studies on doctors' job satisfaction in Malaysia has reached a similar conclusion (Muhammad & Sharifah, 2020). Studies done by Omar et al, (2009) on government nurses, Jasmani et al, (2011) among physicians in National Heart Institute (IJN), Idris et al, (2014) on specialist doctors intent to leave public service, Aidalina and Aniza, (2015) on the physicians leaving public hospitals to private sector healthcare centers, Sharifah and Norwati, (2016) on family physicians in Malaysia and a more recent study by Muhammad and Sharifah, (2020) on physicians' intention to leave government hospitals identified job dissatisfaction to be the main contributor to employer's failure to retain physicians. The aforementioned studies in Malaysia identified pay, promotion, rewards and other personal factors to be the cause of job dissatisfaction among physicians.…”
Section: Employee Retentionmentioning
confidence: 65%
See 3 more Smart Citations
“…Studies on doctors' job satisfaction in Malaysia has reached a similar conclusion (Muhammad & Sharifah, 2020). Studies done by Omar et al, (2009) on government nurses, Jasmani et al, (2011) among physicians in National Heart Institute (IJN), Idris et al, (2014) on specialist doctors intent to leave public service, Aidalina and Aniza, (2015) on the physicians leaving public hospitals to private sector healthcare centers, Sharifah and Norwati, (2016) on family physicians in Malaysia and a more recent study by Muhammad and Sharifah, (2020) on physicians' intention to leave government hospitals identified job dissatisfaction to be the main contributor to employer's failure to retain physicians. The aforementioned studies in Malaysia identified pay, promotion, rewards and other personal factors to be the cause of job dissatisfaction among physicians.…”
Section: Employee Retentionmentioning
confidence: 65%
“…Another study by Idris et al, (2014) from the Institute of Health Management reaffirmed that 30% of the medical specialists in government service intend to leave MoH facilities within 3 years. This is found to be persistently increasing in a recent study by Amir and Ezat, (2020), showing 46.8% of the specialist that responded to have intention to leave the government sector.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The phenomenon of HCWs resigning poses a significant obstacle to the advancement of the health care system in any given country, making it a topic of widespread concern [ 14 ]. The increasing number of resignations among HCWs, particularly in the Asia Pacific region, has been reported as the greatest threat to the development and sustainability of a resilient health care system in a recent study [ 15 ]. Despite efforts to increase supply and retain them, the workforce is still struggling to meet public health demands, as demonstrated in Spain and Brazil [ 16 ].…”
Section: Introductionmentioning
confidence: 99%